Interpreting the Correlation Between Inflation and the Skewness of Relative Prices: A Comment on Bryan and Cecchetti - Ball, Laurence; Mankiw, N. Gregory (The Review of Economics and Statistics, 1999)
© 1999 by the President and Fellows of Harvard College and the Massachusetts Institute of Technology